2012
DOI: 10.1007/s11250-012-0148-7
|View full text |Cite
|
Sign up to set email alerts
|

Elephant grass, sugarcane, and rice bran in diets for confined sheep

Abstract: We aimed to evaluate the effects of diets, based on elephant grass or sugarcane as roughage and corn meal or rice bran as energy concentrate, on performance and body composition in terms of diet intake and digestibility. A total of 30 Santa Ines crossbreds (SIC), castrated male sheep with 19.8 ± 2.0 kg initial body weight (BW) were used. Six animals were slaughtered at the onset of the experiment to estimate the initial body composition for the other animals. The remaining 24 animals were distributed in a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…This effect was also observed by Carvalho and Medeiros (2010) who used diets with different energy levels the authors found no difference between treatments for organ weights. These results corroborate with those found by Cutrim et al (2012), this may likely be due to the similar age and initial and slaughter weights of animals. So it can be inferred that the organs development is linked to the animal size and consequently non carcass components are not affected by feeding.…”
Section: Resultssupporting
confidence: 92%
“…This effect was also observed by Carvalho and Medeiros (2010) who used diets with different energy levels the authors found no difference between treatments for organ weights. These results corroborate with those found by Cutrim et al (2012), this may likely be due to the similar age and initial and slaughter weights of animals. So it can be inferred that the organs development is linked to the animal size and consequently non carcass components are not affected by feeding.…”
Section: Resultssupporting
confidence: 92%
“…This may be related to its greater apparent digestibility results of an elevated ruminal retention time, which stimulates the satiety center and limits feed intake (Gomes et al, 2012). Additionally, sugarcane diets have high content of lignin which affects its degradability rate, decreasing dry matter intake as result of high ruminal transit time (Cutrim et al, 2012). Furthermore, elephant grass showed superior nutritional value compared to sugarcane as roughage (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Lamb production in Brazil is based on natural or cultivated pastures (Costa et al, 2011). The seasonality in forage production affects the output supply of uniform carcass to the industry, resulting in an inconstant lamb production scale throughout the year (Cutrim et al, 2012). Fluctuation on dry matter availability and forage quality may modify lambs performance, such as weight gain and fat composition in lamb's body and consequently meat quality, due to the uncertain amount of nutrients offered.…”
Section: Introductionmentioning
confidence: 99%
“…Whole sugarcane (i.e., stalk, juice, tops, and trash) is used extensively in the tropics and subtropics as a roughage source for the production of cattle , Hulshof et al 2012, Pedreira et al 2012, Rotta et al 2014, pigs (Xande et al 2009(Xande et al , 2010, sheep (Magana et al 2009, Cutrim et al 2012, and goats (Cabral et al 2009). Although not for human consumption, it is interesting to note that sugarcane (either processed using cryogenic grinding or pelleting) has been assessed as an additive to the diets of mice (Wang et al 2007(Wang et al , 2012 and cats (Fischer et al 2012) to improve their digestive and, hence, general health.…”
Section: Whole Sugarcanementioning
confidence: 99%
“…While whole sugarcane contains significant amounts of soluble sugars that can support rapid microbial growth in the rumen (Xande et al 2010), the overall nutritional value of whole sugarcane is relatively low compared with other animal feed ingredients (such as corn meal, soybean meal, and rice bran) (Cutrim et al 2012) because of relatively low levels of protein and minerals (Kutty and Prasad 1980), and relatively low digestibility of the polysaccharides in the fibers from the leaves and stalk (Patil et al 1999, Xande et al 2009). However, despite this, the value of whole sugarcane in global animal production cannot be understated; for example, Brazil has the largest commercial cattle herd in the world with more than 217 million cattle (FAOSTAT 2014) and, given its preeminence as a sugarcane producer, it is no surprise that fresh chopped sugarcane is used as the primary source of roughage in finishing diets in a significant proportion (∼15%) of Brazilian feedlots (Oliveira and Millen 2014).…”
Section: Whole Sugarcanementioning
confidence: 99%